Likestilling i akademia - fra kunnskap til endring - Gullvåg Holter, Øystein; Snickare, Lotta (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
What is the state of gender equality in science and technology? Gender Equality in Academia - from Understanding to Change presents the results of a comprehensive research project and program of initiatives at the University of Oslo's Faculty of Mathematics and Natural Sciences. Researchers have examined gender equality within the department, looking at reasons for imbalance, and at what occurs when measures to promote equality are implemented.The book opens with an in-depth study of careers, gender issues and gender balance within academia. The study, based on questionnaires, interviews and follow-up evaluation, provides a new and updated understanding of the daily lives of academics in Norway. Among the topics covered are perceptions of equality and gender balance, effects of male dominance, sexual harassment, gender with respect to publishing, and the relationship between gender and diversity.In addition to presenting new empirical data, the book is also an innovative contribution to theoretical development within gender equality research. In the second part of the book, the authors present three working models that elucidate current mechanisms recreating gender imbalance, and challenges for gender equality. The book's final part consists of analyses of measures taken to increase gender equality within the department and their effects, and what an organization can do to increase gender equality.The range of topics in this book make it relevant for all those concerned with gender equality in research and higher education. Researchers, administrators, students, other practitioners, and politicians will all find this book of interest.Øystein Gullvåg Holter is a professor emeritus at the University of Oslo's Centre for Gender Research. Lotta Snickare is a researcher at both the University of Oslo's Faculty of Mathematics and Natural Sciences and the KTH Royal Institute of Technology in Stockholm.; Hvordan står det til med likestillingen innenfor realfag og teknologi? Likestilling i akademia - fra kunnskap til endring presenterer resultatene fra et omfattende forsknings- og tiltaksprosjekt ved Det matematisk-naturvitenskapelige fakultet ved Universitetet i Oslo. Forskerne har undersøkt likestillingssituasjonen ved fakultetet, sett på årsaker til ulikestilling, og på hva som skjer når man iverksetter tiltak for å fremme likestilling.Boka innleder med en dybdestudie av karriere, kjønn og likestilling i akademia. Studien, som er basert på både spørreundersøkelser, intervjuer og følgeforskning, gir ny og oppdatert kunnskap om forskerhverdagen i norsk akademia. Blant temaene som belyses er syn på likestilling og kjønnsbalanse, effekter av mannsdominans, seksuell trakassering, kjønn og publisering, og hvordan kjønn og mangfold henger sammen.I tillegg til å presentere ny empiri utgjør boka også et nyskapende bidrag til teoriutvikling innen likestillingsforskningen. I bokas del 2 presenterer forfatterne tre arbeidsmodeller som belyser aktuelle mekanismer og utfordringer i likestillingsarbeidet. Deretter trekkes linjen videre til arbeidet for å fremme likestilling. I siste del analyseres tiltakene som ble iverksatt for å øke likestillingen ved fakultetet, hvilke effekter de hadde, og hva en organisasjon kan gjøre for å øke likestillingen. Bredden i boka gjør den relevant for alle som er opptatt av likestilling i forskning og høyere utdanning. Både forskere, ansatte, studenter, praktikere og politikere vil ha stor nytte av boka.Øystein Gullvåg Holter er professor emeritus ved Senter for tverrfaglig kjønnsforskning, Universitetet i Oslo. Lotta Snickare er forsker ved Det matematisk-naturvitenskapelige fakultet, Universitetet i Oslo, og ved Kungliga tekniska högskolan, Stockholm.